Implementing an Online Program to Change Benzodiazepine Prescription: Protocol of a Hybrid Type 1 Cluster-Randomised Trial - Teresa Reis; Helena Serra; Sofia Azeredo; Miguel Xavier (Karger Publishers, 2022)
Introduction: Excessive benzodiazepine (BZD) prescription has long been considered a serious mental health concern in many countries. Many interventions using different methodologies have been implemented to change BZD prescription patterns in primary health care settings, with limited positive results. Objectives: The primary objective of our study was to analyse the effectiveness and implementation process of an intervention aimed at changing BZD prescription patterns in a primary health care setting in Portugal. Methodology: We chose as methodology an effectiveness-implementation hybrid type 1 intervention. Our intervention was based on the development of an online platform, named ePrimaPrescribe, which was delivered using a Digital Behaviour Change Intervention (DBCI), using a two-arm cluster-randomised clinical trial. Results: We primarily aimed to evaluate the effectiveness of our DBCI in changing BZD prescription patterns using the frequency of BZD prescriptions issued per month as an outcome measure. Secondarily, we aimed to analyse the effect of ePrimaPrescribe on antidepressant prescriptions, to study the effect of the platform on diagnosis registration associated with BZDs and antidepressant prescription, and to perform a cost analysis considering the monthly National Health Service spending on BZD co-payments. Finally, we aimed to analyse the implementation process using quantitative and qualitative methods. Conclusion: With this study, we expect to contribute with a cost-effective intervention to change the complex matter of excessive BZD prescriptions, and also to improve insight into the challenges to intervention implementation processes in primary health care settings. We believe that our findings are relevant not only to the specific setting where the study was implemented, but also to all countries where primary health care plays a central role in care provision.